Safe abortion practice and its health related consequences. - Shakya, Rachana (2011)
ABSTRACT: Nepal has got MDG award for reducing Maternal Mortality Rate effectively. It has succeeded to reduce MMR to 229 in 2010 as it was 415 in 2000. Among the major causes of MMR, unsafe abortion is also taken as one of the main factors. According to a study in 2008\2009 in MMR and Reproductive health diseases, 75 of MMR were due to abortion complication. Legalization of Safe Abortion Services and Comprehensive Health Care and easy access of safe abortion has made it to reduce MMR. Among 7 Lakhs of Nepalese pregnant women, 2 Lakhs have intended pregnancy and from them 1 lakh carry out abortion. The increasing trend in abortion utilization shows that more and more women are seeking safe abortion services. This study is conducted to find the present condition of safe abortion practice and to measure the effectiveness and reliability of safe abortion service. Its health related consequences have to be studied as every procedure has its own side effects and complication. So the study is entitled as "Safe Abortion Practice and its Health Related Consequences." The research was conducted in Marie Stopes clinic that provides the safe abortion services with the collaboration of Sunaulo Nepal Parivar which work for SRH among 43 countries worldwide. The main objective of this study is to find the present condition of safe abortion practices and to point out the health related consequences of them and explore the reproductive health of women in the study area. This study has used a descriptive qualitative and quantitative research design and mainly primary data were taken from 40 women of (15-49) years seeking abortion by means of purposive sampling method. The quantitative data are collected from interview schedule and qualitative data are collected from in depth interview and interview. The quantitative data were transcribed manually and qualitative data were analyzed descriptively. The study has showed that there is existence of need of abortion among women due to unmet need or failure of use of contraceptives. Young women are more likely to use contraceptive to space births whereas older women use to limit births. The Government should provide the easy and safe access of aborting unwanted pregnancy with the consent of aborting women. Nepalese women are getting such facility in the society but they are to be made accessible in remote areas as well. Due to advertisements or its awareness, more women are concerned about their health. Male partner seems to be responsible for bringing his partner for abortion service whereas some women visit self to get the service. Women are self deciding to use the method of abortion after the counseling from health trainer. Many of them know the facilities of abortion but lacks further knowledge on it. About its health related consequences, safe abortion method is found to be safe as its name suggests. Heavy bleeding and infection may be the result but it is found to be minimized by using medicine. Aborting women were found to conceive whenever the need or desire of child exists. Awareness on use of contraceptive device and its accessibility also should be increased to encourage safe sex among the high fertility group. Female needs to be generated awareness on importance of education and every female is in utmost need of sexual and reproductive health care as she has to put efforts on the bearing and rearing of child. Male partner must be fully responsible for his act as well. Abortion must not be taken as alternative for family planning. But, there is need of abortion in the community and so as to minimize its consequences, females need to have counseling in the regular use of contraceptive devices or adoption of long term contraception. Moreover, those who are in need of reproduction must understand "Children by Choice" with full responsibility.